1996
DOI: 10.1007/s0021663540587
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration and determination of Sn- and Pb-organic species in environmental samples by SPME and GC-AED

Abstract: A new sample preparation and preconcentration technique - solid phase microextraction (SPME) - is reported for the application of several tinorganic compounds and tetrabutyllead in aqueous samples. The solvent-free procedure is rapid in comparison with liquid-liquid extraction or SFE but also sensitive. Analytical variables of the extraction such as adsorption and desorption time, stirring rate and temperature has been investigated. The determination has been performed by GC coupled with atomic emission detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…There are some novel approaches useful for the analysis of organotins compounds. For example, an alternative technique, SPME, a solvent free analytical process 63,64 and a coupling of multicapillary GC 99 with sensitive element-selective detection have been reported to be successful to the analysis of organotin compounds in environmental samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some novel approaches useful for the analysis of organotins compounds. For example, an alternative technique, SPME, a solvent free analytical process 63,64 and a coupling of multicapillary GC 99 with sensitive element-selective detection have been reported to be successful to the analysis of organotin compounds in environmental samples.…”
Section: Resultsmentioning
confidence: 99%
“…Solid-phase microextraction (SPME) techniques were applied by Moens et al 63 and Tutschku et al 64 to determine butyltin compounds in aqueous samples. The in situ derivatized compounds with NaBEt4 were sorbed on SPME fiber and determined by GC coupled with AED or ICP-MS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tutschku et al [35] preconcentrated and determined organotin and organolead species in environmental samples by SPME and GC-AED. Analytical variables of the extraction such as adsorption and desorption time, stirring rate, and temperature were investigated.…”
Section: Organolead Compoundsmentioning
confidence: 99%
“…The fiber was immersed for 30 min in the sample solution with constant stirring to assure proper extraction of the analytes. It is reported that organotins can also be analyzed in the presence of other metals [15,21,24,26,29,32,35,37,38,49].…”
Section: Organotin Compoundsmentioning
confidence: 99%